Age-related dissociation of sensory and decision-based auditory motion processing - Ludwig, Alexandra A.; Rübsamen, Rudolf; Dörrscheidt, Gerd J.; Kotz, Sonja A. (Frontiers in Human Neuroscience, 2012)
Studies on the maturation of auditory motion processing in children have yielded inconsistent reports. The present study combines subjective and objective measurements to investigate how the auditory perceptual abilities of children change during development and whether these changes are paralleled by changes in the event-related brain potential (ERP). We employed the mismatch negativity (MMN) to determine maturational changes in the discrimination of interaural time differences (ITDs) that generate lateralized moving auditory percepts. MMNs were elicited in children, teenagers, and adults, using a small and a large ITD at stimulus offset with respect to each subject's discrimination threshold. In adults and teenagers large deviants elicited prominent MMNs, whereas small deviants at the behavioral threshold elicited only a marginal or no MMN. In contrast, pronounced MMNs for both deviant sizes were found in children. Behaviorally, however, most of the children showed higher discrimination thresholds than teens and adults. Although automatic ITD detection is functional, active discrimination is still limited in children. The lack of MMN deviance dependency in children suggests that unlike in teenagers and adults, neural signatures of automatic auditory motion processing do not mirror discrimination abilities. The study critically accounts for advanced understanding of children's central auditory development.